Law of Obligations in Light of the Bogemian Diplomatic Documents of the Thirteenth Century - Naďa Štachová (Journal on European History of Law, 2011)
The paper focuses on the presentation of representative examples from the diplomatic material of the late thirteenth century, which contains the evidences to the characteristic relationships (mainly emptio and venditio) in the sphere of law of obligation in the Czech lands generally. The emphasis is placed on the encroachment of Roman law elements in these texts and their confrontation with the provincial (domestic) law as well as on their value assignment for the legal historical studies